PENERAPAN MEDIA SIMULASI PHET TERHADAP HASIL BELAJAR KONSEP DASAR IPA MAHASISWA TADRIS IPA IAIN PALU - Arda Arda (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2020)
This research is pre experimental research. It aims to find out the result of students learning on forces and Newton’s laws by using PhET simulation media. Subject of this research were 18 students of Tadris IPA who programmed the Basic Concepts of Natural Sciences courses. Descriptive analysis results the mean score of the student learning outcomes before the application of PhET simulation media were 12.67 and after treatment through of PhET simulation media were 15.78. The gain based on the results of data analysis using the gain normalization were 0.42. It means that there is improvement on the students of Tadris IPA learning outcomes in medium category.